Resistance, White Fragility, and Fear of the Unknown in Tertiary Settings: A Recipe for Blak Fatigue - Briese, Jennie; Elliott, Lana; Duthie, Deb (Springer, 2024)
Student resistance to learning First Nations Australian histories in core units remains problematic in many tertiary spaces. Resistance usually manifests alongside white fragility, often displayed through defensive and what might be considered aggressive and violent behaviors. Blakademics, First Nations academics in the colony known as Australia, are expected to remain professional in classrooms, according to western expectations of professionalism when faced with such displays of resistance and white fragility. Also contributing to Blak Fatigue, where Blakademics experience similar fatigue associated with worker burnout, however resulting from many factors including racism, are the many non-First Nations academics in tertiary education spaces who view Blakademics as the “go to” for all things First Nations, or worse, refuse to hear our advice in preference of their perceived “expertise.” Often, Blakademics are approached by such colleagues who offer no tangible plans around their requests and express a “fear of getting wrong” as the reason for approaching empty handed. Reciprocity is rarely offered when contributions—such as guest lectures and “what should be in my unit?’—requests are made. Such attitudes from non-Blakademics may be viewed as expressions of white fragility, including an exaggerated fearful and anxious response to embedding First Nations knowledges in curriculum content. As examined in this chapter, white fragility creates additional layers of fatigue for Blakademics, who are usually not allocated workloads, nor compensated, through reciprocity or otherwise, for sharing First Nations knowledges outside of their own classes. This pattern of resistance to taking responsibility for their own knowledge development often leads to mental, emotional, and physical exhaustion (Blak Fatigue) for Blakademics who teach. To combat this, we Blakademics band together in support for our own wellness, and to create strategies enabling our Blak excellence to rise above non-First Nations resistance to change and ...